Intervensi Edukasi untuk Pemberdayaan Pendamping Keluarga ODGJ: Meningkatkan Peran Aktif dalam Perawatan Kesehatan Mental di Komunitas - Rahmatika, Qory Tifani; Ramadhan, Muhammad Putra; Masfi, Achmad; Aditya, Ronal Surya (Jurnal Abdimas Kesehatan (JAK), 2025)
Family caregivers play a crucial role in the care of individuals with mental disorders (ODGJ), yet they often lack adequate education and support. This limitation can diminish their effectiveness in providing necessary care and assistance. The purpose of this community service initiative is to assess the effectiveness of educational interventions in empowering family caregivers of ODGJ and enhancing their active roles in community mental health care. The intervention began with a pre-test to assess the knowledge, attitudes, and roles of health cadres, followed by education through lectures, videos, interactive discussions, and communication simulations. Subsequently, free health screenings were conducted for health cadres, individuals with mental disorders (ODGJ), and former ODGJ as part of a physical and mental health promotion initiative. The results of this community service activity showed a significant increase in knowledge and attitudes, focusing on the feelings, attitudes, and motivations of caregivers in their roles as family supporters. The educational intervention successfully improved caregivers' competence in the early detection of mental health issues, as well as their roles and responsibilities as mental health cadre. This improvement also led to better quality support for ODGJ and reduced pressure on community mental health services. The educational program proved effective in empowering family caregivers of ODGJ, and it is recommended to further develop and expand this program to reach more caregivers and communities.